IMPROVING THE PERFORMANCE OF SPEED AND STRENGTH ABILITIES OF ATHLETES AGED 11-12 YEARS BASED ON THE USE OF A SET OF SPECIAL EXERCISES - Ubbiev Bakhyt Amangeldievich (Web of Journals Publishing, 2024)
The article presents the material of the results of a pedagogical study devoted to improving the development of speed and strength abilities of young athletes aged 11-12 years of the second year of study in a specialized sports school. The material of the article contains special tools and methods implemented in special complexes and the results obtained at the end of the study.
Keywords: young athletes aged 11-12, exercise complexes, speed and strength abilities, means, methods.